A scoping review to characterize bridging tasks in the literature on aging with disability - Emily Joan Nalder; Tyler M. Saumur; Zinnia Batliwalla; Luis Salvador-Carulla; Michelle Putnam; Andria Spindel; Erica Lenton; Hamdi Hussein (BMC, 2020)
Abstract Background Bridging involves improving knowledge sharing and collaboration across different fields, such as aging and disability. The objectives of this review were to describe: 1) the contexts where bridging has occurred in relation to delivery of health services for adults aging with neurological or developmental conditions; and 2) characterize and map bridging tasks, stakeholders involved, and outcomes discussed in peer-reviewed literature. Methods Seven databases were searched around the core concepts of "bridging," "aging," and "disability." In total, 10,819 articles were screened with 49 meeting the inclusion criteria of discussing aging with developmental or neurological disability, explicitly describing bridging tasks, published in English and a peer-reviewed publication. Bibliographic information, sample characteristics, and data on bridging was extracted and included in the qualitative synthesis. Results Intellectual and/or Developmental disabilities were the most studied population (76% of articles), and most articles were published in the United States (57%). Twenty-two bridging tasks were identified, and categorized into three domains: health and social service delivery (e.g., care coordination tasks), policy (e.g., policy change), and research and training (e.g., mentoring). Stakeholders involved ranged from health care professionals to policy makers and organizations in aging and disability services. Conclusions The resulting matrix will assist in the specification of bridging in research and practice. Future work should evaluate specific models of bridging and their effects on health service delivery.